Advancing the Mainstreaming of Millet in Odisha’s Agrifood System - Kumar, Shalander; Das, Abhishek; Afari-Sefa, Victor; Sawargaonkar, Gajanan; Roul, Pravat Kumar; Padhee, Arabinda Kumar (International Crops Research Institute for the Semi-Arid Tropics, 2024)
Millets holds immense promise as one of the key strategies in addressing several critical challenges that Odisha’s agrifood system faces today, including malnutrition, rural poverty, and the impacts of climate change. During recent years, the state has made significant progress in promoting sustainable agriculture, with millets emerging as a crucial component of the agrifood system for this transformation. Recognizing the potential of millets to enhance nutritional outcomes, improve climate resilience, and support the livelihoods of smallholder farmers, the Government of Odisha has undertaken commendable efforts to promote millet cultivation1 since 2017-18 through initiatives such as the Odisha Millets Mission (OMM), which was later redesigned as Shree Anna Abhiyan, promotion of non-ragi millet under MUROMillet in upland regions of Odisha project, Mission Shakti among others. These efforts have led to notable successes, particularly in increasing millet production, raising awareness about their nutritional, economic, and environmental benefits, increased consumption and employment opportunities, especially for rural women. As Odisha continues to build upon these achievements, there is a need to identify levers for harnessing the full potential and advancing the mainstreaming of millets within the agrifood system from the production to consumption continuum, including the rural-to-urban ecosystem. By integrating millets more deeply into the agrifood system by targeting potential upland and midland ecologies, the state can drive forward a vision of sustainable agricultural practices, resilient and strengthened local food systems, and improved nutritional security. This policy brief seeks to offer insights and potential strategies to fully realize the potential of millets in Odisha State. It emphasizes the importance of collaborative approaches that engage the government, farmers, the private sector, and civil society stakeholders in creating a more inclusive and resilient agrifood system. It is intended to complement and strengthen ongoing government initiatives by offering evidence-based policy recommendations that build upon the progress already achieved.